Design of Key Joint Reducer for Heavy-duty Teleoperation Manipulator - Zhou Zhenguo; Bai Xiaowei; Zhou Zibo (Jixie chuandong)
It is one of the important tasks of the remote operation to perform internal maintenance in the nuclear fusion reactor by the teleoperation manipulator. Because of the key joint of the manipulator will bear excessive load during maintenance,and the main reducer of the manipulator must have a self-locking function,and special functional requirements such as space for cable channels are reserved in the middle of the main reducer. The 2 K-H NN multi-planetary gear mechanism is used as a model to analyze the constraints and design conditions. The number of tooth combinations satisfying the conditions are selected through programming and the calculation of the load on dangerous gear and transmission efficiency is verified. A design Scheme of heavy-duty reducer with high-capacity,compact structure,self-locking function is obtained.